(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2020)
Introduction: Since the first detection of corona virus disease (COVID-19) cases in Dhaka, Bangladesh on 8 March, 2020, numbers are rising alarmingly. Clinical data on COVID-19 in Bangladesh is lacking. We report early findings on demographic profile, clinical presentations and short-term clinical outcomes of confirmed COVID-19 patients admitted in a large teaching hospital in Dhaka, Bangladesh with preliminary analyses of their association with mortality. Materials and Methods: In this retrospective cross-sectional study, we included reverse transcription polymerase chain reaction (RT-PCR) confirmed COVID-19 patients aged ≥ 15 years, who were admitted in Dhaka Medical College Hospital (DMCH) between May 2 and 15, 2020, the first two weeks when DMCH started admitting COVID-19 patients. Data were collected between May 25 and 29, 2020 from patients or their attendants through telephone interview by a structured questionnaire, after having appropriate consent, irrespective of outcome. One hundred and eight consecutive patients met inclusion criteria through convenient sampling from ward registrar, 102 patients could be reached over phone and data from two patients were discarded in the data cleaning process. The statistical analysis was done by the Statistical Package for the Social Sciences (SPSS) version 22.0. Results: Among the total participants (n=100), mean age was 41.7±16.3 years, 63% were male and 60% patients had positive contact history. Appearance of symptom to hospital admission time was a median of 6 days (range 1 to 21 days) and mean hospital stay was 7.77 ± 5.62 days. Predominant presenting symptoms were fever (69%), cough (54%), breathlessness (41%), fatigue (40%), anorexia (26%) and diarrhea (19%). Hypertension (21%), diabetes mellitus (16%), heart diseases including ischemic heart disease (IHD) (8%) and renal diseases including chronic kidney disease (CKD) (8%) were frequent comorbidities. Ten out of hundred patients died. Older age (p= 0.001), male sex (p= 0.007), smoking (p= 0.001), breathlessness (p=0.001) and presence of comorbidities (p= < 0.05) were significantly associated with mortality. Conclusion: Frequent positive contact history and significant association of breathlessness, smoking and comorbidities with mortality in our study reinforces that abiding by the prevention and containment process, smoking cessation, ensuring proper oxygen therapy and addressing comorbidities adequately are very important measures to mitigate COVID-19 in Bangladesh like the rest of the world. J Bangladesh Coll Phys Surg 2020; 38(0): 29-36